2019
DOI: 10.1177/0192513x19881186
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Choices of Highly Educated Employed Women with two Children Under the Universal Two-child Policy

Abstract: This study focuses on urban women who were born in the 1970s and 1980s, and who gave birth during the transformation of China’s family planning policy. We conducted 22 interviews with highly educated women who had given birth to two children each, and who were employed full time. We examined why the respondents had decided to have a second child and how their reproductive choices responded to the policy changes. We found that their reproductive choices were a result of the intersection between state policy int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Scholars have also attempted to focus their research on one perspective. Economic factors are the focus of current research, with Lan (2021) demonstrating that women with better socio-economic status and those who were born into better-off families show a relatively strong desire to have children, and Shen and Jiang (2020) investigating highly educated women and finding that their fertility choices are the result of the intersection of state policy interventions and career choices. Urban-rural differences have captured the attention of many scholars as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have also attempted to focus their research on one perspective. Economic factors are the focus of current research, with Lan (2021) demonstrating that women with better socio-economic status and those who were born into better-off families show a relatively strong desire to have children, and Shen and Jiang (2020) investigating highly educated women and finding that their fertility choices are the result of the intersection of state policy interventions and career choices. Urban-rural differences have captured the attention of many scholars as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have investigated the impact of universal TCP on maternal-neonatal outcomes. For example, the impact of birth policy changes on pregnancy outcomes 8 , the sex ratio at birth 3 , maternity care 9 , maternal risk factors and pregnancy complications 12 , C-section rate 13 , women’s reproductive decision 14 , maternal-neonatal outcomes 15 , and prevalence of congenital defect 7 has been reported. However, limited studies have reported the effect of universal TCP on maternal age pregnancy outcomes in women with AMA 7 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The investment continued after the singleton girls become mothers (Zhang et al., 2019). The limited number of children that the respondents’ parents were allowed to have under the one‐child policy means that it is now possible for them to provide childcare support for their only children (Shen & Jiang, 2020). This empowers singleton girls in the transition to motherhood, as they can maintain career upward mobility or salary increases soon after having a second child.…”
Section: Resultsmentioning
confidence: 99%